Antrodia camphorata inhibits metastasis and epithelial-to-mesenchymal transition via the modulation of claudin-1 and Wnt/β-catenin signaling pathways in human colon cancer cells. (17th August 2017) - Hseu, You-Cheng; Chao, Yu-Hsien; Lin, Kai-Yuan; Way, Tzong-Der; Lin, Hui-Yi; Thiyagarajan, Varadharajan; Yang, Hsin-Ling
Abstract: Ethnopharmacological relevance: Antrodia camphorata (AC) is a well known traditional Chinese medicinal mushroom in Taiwan, has been used to treat various diseases including cancer. Materials and methods: In this study, we investigated the anti-metastatic and anti-EMT properties of a fermented culture broth of AC in human colon SW480 claudin−1- and metastatic SW620 claudin−1+ cancer cells in vitro. Results: AC down-regulates claudin-1 and inhibits the proliferation and colony-formation abilities of both SW620 claudin−1+ and SW480 claudin−1- cells. In highly metastatic SW620 claudin−1+ cells, non-cytotoxic concentrations of AC significantly inhibited migration/invasion, accompanied by the down-regulation of MMP-2 and MMP-9 proteins. AC decreased nuclear translocation of Wnt/β-catenin through a GSK3β-dependent pathway. AC consistently inhibited EMT by up-regulating the epithelial and downregulating the mesenchymal marker proteins. In SW480 claudin−1- cells, AC suppressed migration/invasion potentially through the inhibition of the PI3K/AKT/NFκB signaling pathways without altering the expression levels of β-catenin and GSK3β proteins. Conclusion: Altogether, this study demonstrates the anti-metastatic and anti-EMT activities of AC, which may contribute to the development of a chemopreventive agent for colon cancer. Graphical abstract: